Amorphous carbon interlayers for gold on elastomer stretchable conductors - Manzoor, M.U. (Journal of Physics D: Applied Physics, 2019)
No === Gold on polydimethylsiloxane (PDMS) stretchable conductors were prepared using a novel approach by interlacing an hydrogenated amorphous carbon (a-C : H) layer between the deposited metal layer and the elastomer. AFM analysis of the a-C : H film surface before gold deposition shows nanoscale buckling, the corresponding increase in specific surface area corresponds to a strain compensation for the first 4–6% of bi-axial tensile loading. Without this interlayer, the deposited gold films show much smaller and uni-directional ripples as well as more cracks and delaminations. With a-C : H interlayer, the initial electrical resistivity of the metal film decreases markedly (280-fold decrease to 8 × 10−6 Ω cm). This is not due to conduction within the carbon interlayer; both a-C : H/PDMS and PDMS substrates are electrically insulating. Upon cyclic tensile loading, both films become more resistive, but return to their initial state after 20 tensile cycles up to 60% strain. Profiling experiments using secondary ion mass spectroscopy and x-ray photoelectron spectroscopy indicate that the a-C : H layer intermixes with the PDMS, resulting in a graded layer of decreasing stiffness. We believe that both this graded layer and the surface buckling contribute to the observed improvement in the electrical performance of these stretchable conductors.